Examining technical and behavioural possibilities in developing fleet services in the machinery manufacturing context - Korhonen, Tuomas; Stormi, Kati; Laine, Teemu; Liew, Angela (Proceedings of Pragmatic Constructivism, 2017)
This paper shows how service development for a machinery fleet can be supported by financial analyses. In particular, the paper shows how service managers’ work can be supported by accounting information. The paper draws upon an interventionist case study at a machinery manufacturer in Finland. The paper contributes to the literature on pragmatic constructivism by extending its usability into new groups of managerial actors in the timely context of service development for machinery fleets. Moreover, the paper contributes to the servitization literature, by showing ways to identify technical and behavioural possibilities and to overcome related difficulties in manufacturing companies’ transition to service business.